Term Structure Movements and Pricing Interest Rate Contingent Claims - HO, THOMAS S. Y.; LEE, SANG‐BIN (Journal of Finance, 1986)
ABSTRACT This paper derives an arbitrage‐free interest rate movements model (AR model). This model takes the complete term structure as given and derives the subsequent stochastic movement of the term structure such that the movement is arbitrage free. We then show that the AR model can be used to price interest rate contingent claims relative to the observed complete term structure of interest rates. This paper also studies the behavior and the economics of the model. Our approach can be used to price a broad range of interest rate contingent claims, including bond options and callable bonds.